ETIKA DALAM PENDIDIKAN: PERESPEKTIF HADIST TARBAWI DAN IMPLEMENTASINYA DI ERA DIGITALISASI - hafid; Labibul Wildan (Qolamuna : Jurnal Studi Islam, 2025)
This study aims to discuss about "Islamic education does not only focus on the aspect of knowledge, but also on the formation of morals and ethics based on the values of the Qur'an and Hadith. In the digital era, challenges related to ethical and moral behavior are increasingly complex, given the development of information and communication technology that influences the way of learning and interacting. This study aims to examine the application of Islamiceducational ethics through the perspective of Hadith in overcoming educational challenges in the digital world. Using a literature review method, this study explores how Hadith can be a guideline in dealing with problems such as the spread of hoax information, cyberbullying, and the decline in the quality of social interaction. This study also develops practical guidelines for educators and students in implementing Hadith-based educational ethics in cyberspace. The results of the study indicate that education based on Hadith values can help create a more ethicaland moral educational environment in the digital era, as well as guide the younger generation to develop good character through the wise use of technology. Keywords: Islamic Education, Education Ethics, Tarbawi Hadith, Digital Era.